Correlation of Motor Competence and Social-Emotional Wellbeing in Preschool Children - Salaj, Sanja; Masnjak, Mia (Frontiers in Psychology, 2022)
Introduction: Relations of motor skills to different developmental domains, i.e. cognitive, emotional and social domain, are well documented in research on children with poor motor competence such in children with disabilities. Less conclusive evidence on interaction of motor to social or emotional development can be seen in research including typically developing children. Purpose of this study is to determine correlation between motor skills and social-emotional functioning in typically developing preschool children, and to determine differences in social-emotional functioning in children with different level of motor competence. Methods: One hundred twenty-five preschool children participated in this study (67 boys, 58 girls, average age 5.1 years). To assess children's motor skills, we used the Test of Gross Motor Development – Second Edition that measures locomotor and object-control skills. To screen child's social and emotional functioning we used the Ages and Stages Questionnaire - Social Emotional: Second Edition. Spearman correlation analysis was used to determine association between motor skills and social-emotional functioning. Difference in social-emotional functioning between groups of preschool children of High and Low motor competence was calculated using Mann-Whitney U test. Results: Main results of this study show weak correlation of child's motor skills to social-emotional functioning. Furthermore, preschool children of High and Low motor competences do not differ in risk for social and emotional difficulties. Conclusion: Further research including typically developing children is needed to have more conclusive evidence on interaction of motor to social or emotional development.